Microbiological rationale for the use of Abigel-gel in conservative treatment inflammatory periodontal diseases - Любченко, Ольга Валеріївна; Велігоря, Ірина Євгеніївна; Полякова, Світлана Віталіївна; Іванов, Олександр Євгенович; Циганова, Наталія Борисівна; Пушкар, Людмила Юріївна; Циганова, Ірина Валеріївна (Actual Dentistry, 2020)
Summary. A comparative assessment of the antamicrobial properties of the gel herbal preparation Abigel was made; the comparison group consisted of Fitoron and President-gel with chlorhesidine. The studies were carried out using standard test cultures of gram-positive and gram-negative bacteria belonging to different taxonomic groups: Staphylococcus aureus ATCC 25923, Esсherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Bacillus subtilis ATCC6633, Proteus vulgaris ATCC 4636. The antifungal effect of the sample was investigated on the reference strain Candida albicans ATCC 885-653 (4, 5, 6). Also used clinical museum strains (Staphylococcus epidermidis, Enterococcus faecalis, Haemophillus influenzae, Streptococcus pyogenes, Streptococcusmutans, Neisseria sp). President gel with chlorhexidine, Fitoron and Abigel gel have pronounced anti-microbial properties in relation to the investigated test cultures of microorganisms. Abigel is an effective method of vibor in the conservative treatment of inflammatory periodontal diseases. The method of treatment and prevention of inflammatory periodontal diseases with the use of Abigel is quite effective and justified in complex treatment, and as an independent method. Key words: Inflammatory periodontal diseases, Abigel gel, President gel with chlorhexidine, Fitoron.